Barriers and facilitators to non-pharmacological management of metabolic dysfunction-associated steatotic liver disease: a qualitative evidence synthesis - Yilmaz, Yusuf (Frontiers in Pharmacology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) represents a significant global health concern, with limited pharmacological options despite extensive research efforts. While the recent conditional approval of resmetirom for metabolic dysfunction-associated steatohepatitis with significant or advanced fibrosis has marked a major therapeutic milestone, lifestyle interventions–primarily dietary modifications and structured physical activity–remain the foundation of MASLD management for most patients. However, integrating these non-pharmacological strategies into routine clinical practice remains a significant challenge. In this qualitative evidence synthesis, we searched the PubMed, Scopus, ScienceDirect, and Google Scholar databases to identify and categorize the principal barriers and facilitators influencing the implementation of lifestyle interventions in MASLD care. The analysis identified 67 barriers and 64 facilitators. To address these multifaceted challenges, we propose a multidisciplinary management framework anchored in six core principles: (1) strategic integration of diverse professional expertise with clear role delineation; (2) patient-centered interventions that address both societal and individual barriers while leveraging facilitators; (3) early preventive measures to halt disease progression prior to the development of significant fibrosis; (4) tailored approaches responsive to disease severity and comorbidities; (5) optimized monitoring protocols with specific thresholds for intervention adjustment; and (6) judicious incorporation of digital health technologies, accounting for variability in digital literacy. We conclude that understanding both barriers and facilitators is essential for developing adaptable, patient-centered interventions. Our findings may provide a roadmap for addressing implementation challenges in non-pharmacological MASLD management, emphasizing the importance of preventive, tailored, multidisciplinary approaches that begin early and evolve with disease progression.